2014
DOI: 10.1155/2014/524650
|View full text |Cite
|
Sign up to set email alerts
|

A Platform for Screening Potential Anticholinesterase Fractions and Components Obtained from Anemarrhena asphodeloides Bge for Treating Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease characterized by progressive memory loss and cognitive impairment. Cholinesterase inhibitors are widely used for the symptomatic treatment of Alzheimer's disease to enhance central cholinergic transmission. In this study, a bioactivity-oriented screening platform based on a modified Ellman's method and HPLC-QTOF MS technique was developed to rapidly screen active agents of Anemarrhena asphodeloides Bge. The 60% ethanol fraction from an ethyl acetate extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…37 These compounds have various pharmacological properties, such as promoting learning and memory, 38 reducing in ammation and oxidative stress, 39,40 lowering Aβ levels, inhibiting tau protein hyperphosphorylation, 41,42 and decreasing apoptosis in neuronal cells. 43,44 Screening based on Ellman's method and HPLC-QTOF MS technique revealed that Zhimai steroidal saponins exhibit moderate or weak AChE inhibitory activity, 45 indicating their potential as an anti-AD drug. On the other hand, Diosgenin exerts its therapeutic effect on AD by modulating NOX 4/NOX 4-mediated oxidative stress and in ammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…37 These compounds have various pharmacological properties, such as promoting learning and memory, 38 reducing in ammation and oxidative stress, 39,40 lowering Aβ levels, inhibiting tau protein hyperphosphorylation, 41,42 and decreasing apoptosis in neuronal cells. 43,44 Screening based on Ellman's method and HPLC-QTOF MS technique revealed that Zhimai steroidal saponins exhibit moderate or weak AChE inhibitory activity, 45 indicating their potential as an anti-AD drug. On the other hand, Diosgenin exerts its therapeutic effect on AD by modulating NOX 4/NOX 4-mediated oxidative stress and in ammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…has the function of regulating neurotransmitters levels, inhibiting hippocampal neuron apoptosis, and attenuating cerebral ischemia injury and cognitive deficits [ 21 24 ]. Anemarrhena asphodeloides Bunge has been verified to have cholinesterase inhibitory activity, and it could inhibit neuroinflammation and remove oxygen free radicals to improve learning and memory abilities [ 25 , 26 ]. Paeoniae Radix Rubra has also been demonstrated to have inhibitory effects on thrombus formation, as well as anti-inflammatory and antioxidative properties to reduce neurotoxic injury [ 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…has the function of regulating neurotransmitters levels, inhibiting hippocampal neuron apoptosis, and attenuating cerebral ischemia injury and cognitive de cits [21][22][23][24]. Anemarrhena asphodeloides Bunge has been veri ed to have cholinesterase inhibitory activity, and it could inhibit neuroin ammation and remove oxygen free radicals to improve learning and memory abilities [25,26]. Paeoniae Radix Rubra has also been demonstrated to have inhibitory effects on thrombus formation, as well as anti-in ammatory and antioxidative properties to reduce neurotoxic injury [27][28][29].…”
Section: Introductionmentioning
confidence: 99%